Service quality in restaurants operating in a rural area - Kukanja, Marko (Academica turistica, 2019)
The purpose of this paper was to investigate service quality in restaurants operating in the rural area of Slovenian Istria. The dinerserv tool was used as a research instrument. The research sample consisted of 25 restaurant facilites and 250 valid questionnaires completed by domestic guests.
Keywords: gostilne; gostinstvo; kvaliteta; podeželje; restaurant industry; restavracije; rural areas; service quality; Slovenian Istria; slovenska Istra